Determinants of Multivitamin Supplement Consumption in College Students During The Covid-19 Pandemic - Azizah, Rofiqotin; Syahrul, Fariani; Saputra, Firman Firdauz; Ssekalembe, Geofrey (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2023)
One of the areas affected by the Covid-19 pandemic is Sumenep Regency. The vulnerable population is adolescence. Preventive measures that can be taken to maintain exposure to Covid-19 are the consumption of multivitamin supplements. The purpose of this study was to analyze the determinants that affect the consumption of multivitamin supplements for students in Sumenep Regency during the Covid-19 pandemic. Type of quantitative research with Cross Sectional study design. The sampling technique uses non probability sampling.  The study was conducted online with a total of 300 respondents. The research was conducted online. The dependent variable is the consumption of multivitamin supplements. Independent variables are socio-demographic factors, social support and behavior in terms of planned behavior theory. The analysis was performed using multiple regression performed on SPSS 18. The determinant of multivitamin supplement consumption in students in Sumenep Regency is monthly income (aExp (B) 2,233; CI 1.152-4.329), information sources (aExp(B) 2.296; CI 1.091-4.833), residence category (aExp(B) 0.282; CI 0.080-0.989), knowledge (aExp(B) 2.843; CI 1,636-4,939), Family Emotional Support (aExp(B) 2,659; CI 1.422-4.971), Family Informational Support (aExp(B) 4.507; CI 1.824-11.135). It is important to always provide support to adolescents to regularly take multivitamin supplements in an effort to prevent the transmission of COVID-19